A Case Series Report on Congenital pulmonary airway malformation – antenatal diagnosis and post-natal follow up - Guha Roy, Anik; Sahu, Suparna; Mandi, Khokan (International Journal of Medical Research and Review, 2024)
Congenital pulmonary airway malformation is the most commonly detected congenital lung defect in the ante-natal period. CPAM is a rare developmental, non-hereditary dysplastic lung lesion. No obvious association with maternal age, race or exposure to any given factor could be ascertained. It has an incidence about 1:1500-4000 of all live birth. We present four cases of congenital pulmonary airway malformation: antenatally detected by ultrasound with their follow up in post-natal period. Three of them have normal uneventful post-natal period. One child was normal for six months of age then developed frequent respiratory tract infection. Key words-CPAM, USG, cystic lung lesion